(untitled) (Research, Society and Development, 2022)
This study is part of a larger investigation concerning the sickness absenteeism of legislative workers in Brazil. The article aimed to evaluate and characterize the psychosocial risk factors, which will be used in absenteeism investigation. 400 workers from three Legislative Houses were recruited to fill an online protocol for assessing psychosocial risk factors at work (PROART). From ten factors that comprise the four scales of PROART, only the mental exhaustion factor (ME) was recognized as a medium-level risk by the workers. This condition represents a state of alert or critical situation of the psychosocial factors that requires interventions in short and mid-term. The multiple linear regression model for psychological damage (SD) presented the most expressive value (R²=0.587, p-value<0.05), indicating that the lack of meaning at work (FST), ME and the lack of recognition (FR) were able to explain 58.7% of the SD variability. The psychosocial environment, in general, showed moderate levels of workplace tension, however, it was evidenced critical points with significant potential to threaten the mental and physical health of public workers.